2015
DOI: 10.1016/j.electacta.2015.08.103
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrocatalytic Oxidation of Cu-cyanides and Cu-EDTA at TiO2 nanotube electrode

Abstract: A B S T R A C TOxidation of Cu-cyanides and Cu-EDTA complexes by a photoelectrocatalytic process was investigated at the TiO 2 nanotube matrix electrode. The results indicated that Cu oxides were deposited onto the TiO 2 nanotube anode in the individual oxidation of Cu-cyanide complexes with the conversion of CN À into OCN À . In the case of Cu-EDTA, Cu-EDTA was efficiently oxidized at the TiO 2 nanotube anode and liberated Cu 2+ was deposited onto the cathode with only little amount of Cu oxides deposited ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 34 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…This is associated with the generation of electron-hole pairs on the surface of the semiconductor 5,38 . As it has been previously reported in the literature 5,[22][23][24] , photocatalytic oxidation of CNon TiO 2 occurs primarily due to direct charge transfer. 64% CNdegradation after 2 hr.…”
Section: Photoelectrocatalytic Oxidation Of Cyanidementioning
confidence: 76%
See 1 more Smart Citation
“…This is associated with the generation of electron-hole pairs on the surface of the semiconductor 5,38 . As it has been previously reported in the literature 5,[22][23][24] , photocatalytic oxidation of CNon TiO 2 occurs primarily due to direct charge transfer. 64% CNdegradation after 2 hr.…”
Section: Photoelectrocatalytic Oxidation Of Cyanidementioning
confidence: 76%
“…Nonetheless, the mechanisms of action of N and F as doping agents in TiO 2 are strongly dependent on the methods for the synthesis and preparation of the photocatalysts. Furthermore, even though the use of this type of semiconductor materials for the photoelectrocatalytic oxidation of cyanide represents a promising technology for the decontamination of natural water sources, it has hardly been investigated 5,22 . To our knowledge, the studies reported in the literature primarily deal with the electrooxidation of CNby direct electron transfer 23,24 using expensive electrodes, which compromises the economical feasibility of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Hg|HgO is mainly the dissolution peak of the Cu anode. There is also an anode dissolution peak E at 1.0 V vs. Hg|HgO, which is the oxidation peak of water [32][33][34][35][36][37]. With the increase in the SC content, the intensities of the deposition peaks A, B, and C all increased gradually, indicating that increasing the amount of this additive is beneficial to metal deposition.…”
Section: Effects Of the Additives On The Phase Composition Of The Coamentioning
confidence: 99%
“…The concentration of Cu complexes was tested using a high performance liquid chromatograph (HPLC, 1260, Agilent Technology) with the Hypersil Gold (Thermo Scientific) analytical column, the elution comprised of 8% acetonitrile (v/v)/92% oxalic acid (15 mM) (at pH 3.0, flow rate: 1 mL/min, 25°C, 254 nm) [24]. The total metal ions concentrations in the solution were measured by ICP-OES (700 series Agilent Technology, U.S.A).…”
Section: Analytic Proceduresmentioning
confidence: 99%